Pembingkaian Berita Kongres Luar Biasa Partai Demokrat pada Kompas.com - Selvi Triwahyuni (Neolectura, 2022)
The struggle for power is actually not a new problem in Indonesian politics. Being the general chairman of the party is not only a determinant of various party policy decisions, but has a strong opportunity to be nominated in the presidential election or enter into important structures in Indonesian government institutions. So, it is not something new anymore if the position of the general chairman of the party is a position that is always contested by the party elite. Regarding news, the media must have their own way of framing news. This study aims to find out how Kompas.com frames the news of the Extraordinary Democratic Party Congress for the period 5–6 March 2021. This study uses a constructivist paradigm with a qualitative approach. The research method used in this study is Robert N. Entman's framing analysis, which has two major dimensions, namely selection of issues and highlighting aspects and has four framing elements, namely define problems, diagnose causes, make moral judgments, and treatment recommendations. The results show that Kompas.com places the news of the Extraordinary Democratic Party Congress into political issues. This can be seen from the selection of sources and statements made, as well as the highlighting of the aspects shown, Kompas.com shows the contra side of Moeldoko as the Presidential Chief of Staff, then there is Marzuki Alie who is the Secretary General of the Democratic Party and Darmizal as the Deputy Chair of the Democratic Party Supervisory Commission. Moeldoko was placed as an actor causing problems that have caused a public uproar.